Topological analog signal processing - Farzad Zangeneh-Nejad (Nature Portfolio, 2019)
Analog signal processors could potentially offer faster operation and lower power consumption than digital versions, but are not yet commonly used for large scale applications due to considerable observational errors. Here, the authors demonstrate the unique relevance of topological insulators for improving reliability in such analog processors.